2022
DOI: 10.1111/1440-1681.13673
|View full text |Cite
|
Sign up to set email alerts
|

Hemin mitigates contrast‐induced nephropathy by inhibiting ferroptosis via HO‐1/Nrf2/GPX4 pathway

Abstract: Contrast‐induced nephropathy (CIN) is a common complication with adverse outcome after iodinated‐contrast injection, yet still lacking effective medication. Heme oxygenase‐1 (HO‐1) has been reported to play an important role against renal injuries. Hemin, a HO‐1 inducer and anti‐porphyria medicine, may have a promising effect against CIN. In this study, we aim to investigate the effect of hemin on CIN model and the underlying molecular mechanisms in human proximal tubule epithelial cells (HK‐2). To mimic a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Ferroptosis is a form of programmed cell death that is dependent on iron and is characterized by abnormal mitochondrial structure, accumulation of lipid ROS and GSH. 33 , 34 Previous studies have shown that ferroptosis plays a detrimental role in the development of various forms of AKI, including CIN. To determine the protective effect of BBR against CIN, the inhibitory effect of BBR on ferroptosis was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis is a form of programmed cell death that is dependent on iron and is characterized by abnormal mitochondrial structure, accumulation of lipid ROS and GSH. 33 , 34 Previous studies have shown that ferroptosis plays a detrimental role in the development of various forms of AKI, including CIN. To determine the protective effect of BBR against CIN, the inhibitory effect of BBR on ferroptosis was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The excessive accumulation of intracellular ROS, depletion of reductive GSH and release of intracellular Fe 2+ in large quantities from ferritin together induce ferroptosis 44 . It has been reported that CIN is closely associated with increased ferroptosis 34,45,46 . However, the microscopic morphology of cells undergoing ferroptosis during CIN has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we reason that using different models of injury (iron overload vs. IR) may explain the discrepant results. HO-1 has previously been reported to exert anti-ferroptotic properties [ 48 , 49 , 50 , 51 ]. Here, in corroboration of our previous findings in a model of kidney disease [ 18 ], we report that FtH deficiency leads to marked upregulation of HO-1 following injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a contrast-induced nephropathy (CIN) model, type 1 diabetic rats received intravenous injection of iopromide, heme inhibited ferroptosis by activating HO-1/Nrf2 and upregulating GPX4. They suggested that HO-1 and Nrf2 constitute a positive mutually reinforcing cycle, resulting in self-reinforcement and maintenance of antioxidant capacity 137 . To date, the controversial points of HO-1 in ferroptosis might be dependent on the comprehensive regulation of iron content and antioxidant activity.…”
Section: Ferroptosis-related Regulators Involved In Dkdmentioning
confidence: 99%